2013
DOI: 10.5539/jedp.v3n2p15
|View full text |Cite
|
Sign up to set email alerts
|

Early Child Care Effects on Later Behavioral Outcomes Using a Canadian Nation-Wide Sample

Abstract: This study investigated the effects of child care type, quantity, and quality on later behavioral outcomes (e.g., hyperactivity-inattention, internalizing behavior). We used data from the Canadian National Longitudinal Survey of Children and Youth to examine child care characteristics for children 0-11 months who were using child care (N = 365). Multiple regressions tested the impact of child care, while taking into account child and family variables, on behavioral outcomes at 6-7 years. Interactions between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Babchishin, Weegar, and Romano (2013) compared outcomes for infants in child care with those of a group not in child care, and they found that experience in center-based care predicted hyperactivity/inattention at 6-7 years of age after they controlled for process quality (e.g., caregiver use of praise) and structure quality (e.g., safe environment) of the child care centers. Vandell et al (2010) reported that after they controlled for the quality and type of care, more time in child care predicted more caregiver-reported problem behavior at age 4.5 years and more teacher-and mother-reported problem behavior in kindergarten.…”
Section: Quantity and Quality Of Child Carementioning
confidence: 98%
“…Babchishin, Weegar, and Romano (2013) compared outcomes for infants in child care with those of a group not in child care, and they found that experience in center-based care predicted hyperactivity/inattention at 6-7 years of age after they controlled for process quality (e.g., caregiver use of praise) and structure quality (e.g., safe environment) of the child care centers. Vandell et al (2010) reported that after they controlled for the quality and type of care, more time in child care predicted more caregiver-reported problem behavior at age 4.5 years and more teacher-and mother-reported problem behavior in kindergarten.…”
Section: Quantity and Quality Of Child Carementioning
confidence: 98%
“…A large pool of international research findings have shown that access to formal childcare-provided it is of high quality and for a significant number of hours during the week-is crucial to improving children's outcomes and life chances, even for very young toddlers and infants, especially those from more disadvantaged backgrounds (van Huizen & Plantenga, 2018;Ünver et al, 2018;Petitclerc et al, 2017;Huston et al, 2015;Sibley et al, 2015;Dearing et al, 2015;Havnes & Mogstad, 2011, 2014Lloyd & Potter, 2014;Bauchmüller et al, 2014;Babchishin et al, 2013;Li et al, 2013;Stephen et al, 2011;Penn, 2009).…”
Section: Making the Case For Free Universal High-quality Ecec Provisionmentioning
confidence: 99%
“…Studies that subscribe to evaluation of quality in childcare institutions look for beneficial effects that quality programs can have on the socio-emotional and cognitive development of children (e.g., Bradley, McKelvey, & Whiteside-Mansell, 2011;Landry et al, 2014;Sosinsky & Kim, 2013;Sylva & Pugh, 2011;Thomason & La Paro, 2009). For example, studies conclude that quality early care can facilitate cognitive and language development and social relationships, improve relationships between children and their mothers, and in general lead to long-term positive outcomes in the development of children (Babchishin, Weegar, & Romano, 2013).…”
Section: The "Quality" Of Institutional Childcarementioning
confidence: 99%